2021
DOI: 10.1007/s00401-021-02347-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer stem cells in medulloblastoma by inhibiting AMBRA1 dual function in autophagy and STAT3 signalling

Abstract: Medulloblastoma (MB) is a childhood malignant brain tumour comprising four main subgroups characterized by different genetic alterations and rate of mortality. Among MB subgroups, patients with enhanced levels of the c-MYC oncogene (MBGroup3) have the poorest prognosis. Here we identify a previously unrecognized role of the pro-autophagy factor AMBRA1 in regulating MB. We demonstrate that AMBRA1 expression depends on c-MYC levels and correlates with Group 3 patient poor prognosis; also, knockdown of AMBRA1 red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 103 publications
(165 reference statements)
0
22
0
Order By: Relevance
“… 15 , 16 In addition, recent findings highlighted an important involvement of Ambra1 in cell cycle regulation, in particular controlling the abundance of D‐type cyclins. 28 ,S1,S19 These findings, together with the identification of a c‐Myc/Ambra1/STAT3 oncogenic pathway, 29 pointed at cancer as one major field of study for Ambra1.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 In addition, recent findings highlighted an important involvement of Ambra1 in cell cycle regulation, in particular controlling the abundance of D‐type cyclins. 28 ,S1,S19 These findings, together with the identification of a c‐Myc/Ambra1/STAT3 oncogenic pathway, 29 pointed at cancer as one major field of study for Ambra1.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] However, the function of autophagy in the stemness phenotype is paradoxical, as autophagy plays a dual role in cancer. [6] On the one hand, autophagy sustains the self-renewal and therapy resistance of cancer stem cells; [33,34] on the other hand, loss of autophagy impedes stem cell differentiation and increases tumorigenicity. [35] In glioma stem cells, diverse inducer-mediated autophagy plays distinct roles.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has been demonstrated that autophagy positively regulates stemness in MB cells. Indeed, the expression of the pro-autophagy factor AMBRA1 depends on c-MYC levels, and it is strongly upregulated in Group 3 MB-CSCs[ 58 ].…”
Section: Metabolic Features Of Mb Cancer (Stem) Cellsmentioning
confidence: 99%
“…Moreover, IP6 synergised with Cisplatin, potentiating its cytotoxic activity in vitro and in vivo, and extending survival of the mice[ 55 ] significantly. Finally, pharmacological inhibition of the pro-autophagy factor AMBRA1 affected both the growth and invasion potential of group 3 MB-CSCs profoundly, enhanced by the combination of AMBRA1 and STAT3 inhibition[ 58 ].…”
Section: Targeted Therapies In Mbmentioning
confidence: 99%